Lagrangian investigation on the compound effects of reclamation and proposed tidal barrage to the environmental flow - Wei, Koon Lee; Nur Hidayah Aqilla Zaharuddin (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
Large-scale reclamation at Tekong Island, Singapore and the construction of a tidal barrage across Johor River in Kota Tinggi is expected to alter the local hydrodynamics in Johor River Estuary (JRE) and East Tebrau Strait (ETS). Using fl ow fi eld generated from a set of hyperbolic shallow water equations solved on hierarchical quadtree grid system, Lagrangian particle tracking is performed to examine the individual and combined effects of the above developments on particle fate. Results show that particle escape is highly dependent on the tidal cycle and the initial positions. Stretching of particles is observed in all cases, whereas dispersion occurs only in ETS. While the fl ushing effect in JRE is enhanced after the completion of the above projects, the resident time of particles released in the ETS increases, suggesting potential environmental threat to the already polluted water body.